Primary analysis of EPIK-O/ENGOT-ov61: alpelisib plus olaparib versus chemotherapy in platinum-resistant or platinum-refractory high-grade serous ovarian cancer without BRCA mutation - Konstantinopoulos, Panagiotis A.; Kim, Jae Weon; Freyer, Gilles; Lee, Jung Yun; Gaba, Lydia; Grisham, Rachel N.; Colombo, Nicoletta; Wu, Xiaohua; Sehouli, Jalid; Cruz, Felipe; Cibula, David; Monk, Bradley J.; et al. (Journal of clinical oncology, 2025)
Purpose - Patients with platinum-resistant/platinum-refractory high-grade serous ovarian cancer (HGSOC) without a BRCA mutation have poor prognosis and limited treatment options. We report efficacy and biomarker data from EPIK-O, which investigated alpelisib + olaparib versus single-agent chemotherapy in these patients. - Patients and Methods - EPIK-O was an open-label, phase III trial that randomly assigned patients with platinum-resistant/platinum-refractory HGSOC with no germline or known somatic BRCA mutation 1:1 to alpelisib 200 mg once daily + olaparib 200 mg twice daily or treatment of physician's choice (TPC; paclitaxel 80 mg/m2 once weekly or pegylated liposomal doxorubicin 40-50 mg/m2 once every 28 days). Patients had 1-3 previous systemic therapies. Previous bevacizumab was required (unless contraindicated); previous poly(adenosine diphosphate-ribose) polymerase inhibitors were allowed. Primary end point was progression-free survival (PFS) per RECIST 1.1 (blinded independent review committee [BIRC]). Secondary efficacy end points included overall response rate (ORR; per BIRC), duration of response (per BIRC), and overall survival (OS; key secondary end point). - Results - A total of 358 patients (alpelisib + olaparib [n = 180], TPC [n = 178]) were included. The median follow-up time was 9.3 months. At data cutoff (April 21, 2023), 33 (18.3%) and 30 (16.9%) patients remained on treatment with alpelisib + olaparib and TPC, respectively. The median PFS (BIRC) was 3.6 versus 3.9 months (hazard ratio [HR], 1.14 [95% CI, 0.88 to 1.48]; one-sided P = .84) for alpelisib + olaparib versus TPC. The ORR was 15.6% (95% CI, 10.6% to 21.7%) versus 13.5% (95% CI, 8.8% to 19.4%). The median OS was 10.0 versus 10.6 months (HR, 1.22; 95% CI, 0.87 to 1.71). The safety profile of alpelisib + olaparib was consistent with that observed for the individual agents. - Conclusion - The primary objective, PFS improvement, was not met in EPIK-O. No new or unexpected adverse events were observed. Biomarker analyses provided new insights for responders to alpelisib + olaparib.
Online veröffentlicht: 23. Juli, 2025
Gesehen am 13.11.2025